Characterization and phylogenetic analysis of the complete mitochondrial genome sequence of Lagenaria siceraria, a cucurbit crop - Du, Xuan; Wang, Kuanhong; Tang, Yuying; Wu, Jue; Yang, Xiaofeng; Zhang, Hongmei; Liu, Na; Zhang, Zhaohui (Frontiers in Plant Science, 2025)
Bottle gourd (Lagenaria siceraria)belongs to cucurbit crop and hasunique semi-autonomous organelle genome. Using Illumina short-read and Nanopore long-read sequencing data, we sequenced and annotated the complete mitochondrial genome of L. siceraria. And a comparative phylogenetic analysis was conducted with its close relatives. The mitochondrial genome of bottle gourd is a circular sequence of 357,496 bp with a GC content of 45.03%. It contains 63 genes, including 34 mRNAs, 24 tRNAs, 4 rRNAs, and 1 pseudogene. The rps19 gene is present, but rpl10 is absent. 22,294 bp (6.24%) are repetitive sequences. 497 RNA editing sites were identified. 45 homologous fragments (40,579 bp, 11.35%) were shared with the chloroplast genome. Phylogenetic analysis revealed that C. maxima, C. sativus, C. lanatus, and L. acutangula are closely related to bottle gourd. Gene arrangement analysis indicated that L. acutangula exhibits the highest collinearity with L. siceraria compared to other cucurbit crops. However, genome size and repetitive sequences are most similar to watermelon. Nearly all Ka/Ks ratios <1.0 suggest stabilizing selection in protein-coding genes. These findings provide a foundation for further understanding the evolutionary relationships within cucurbit crops.